دور الاجهزه العليا للرقابة المالية والمحاسبية في التنمية المستدامه - خولة حسين حمدان (مجلة الغري للعلوم الاقتصادية والادارية)
المستخلص قد يتمكن الجهاز الاعلى للرقابة من مساعدة صانعي الق ا رر الاست ا رتيجي ضمن الحكومة اذ يقوم بتدقيق مجالات الاقتصادية والبيئية والاجتماعية والمؤسسية وقياس التقدم الذي احرز من خلال وضع المؤش ا رت مقابل الاهداف، اذ يستند البحث على فرضية مفادها ان الافصاح عن نتائج تحليل مؤش ا رت التنمية المستدامة ضمن ابعادها (الاقتصادية والاجتماعية والبيئية والمؤسسية) من قبل الجهاز الاعلى للرقابة المالية والمحاسبية يساعد في اتخاذ الق ا ر ا رت الرشيدة التي تحافظ على حاجات الاجيال الحالية والمستقبلية، اذ تضمن البحث في الجانب النظري الرقابة على التنمية المستدامة اما الجانب العملي تحليل نتائج مؤش ا رت التنمية المستدامة لجمهورية الع ا رق وانتهى البحث بمجموعة من الاستناجات والتوصيات . The role of SAIs financial and accounting control in Sustainable development Assistant. Prof .Dr Khawla H. Hamdan Baghdad University / Post –Graduate Institute for Accounting and Financial Studies Abstract SAI may be able to assist strategic decision-makers within the government as the audited economic, environmental and social areas and Institutional then the progress that has been made through the development of indicators with objectives, as research is based on the premise that disclosure of the results of the analysis of indicators of sustainable development within its dimensions economic, social and environmental and institutional) by the supreme organ of financial and accounting control helps in making wise decisions that keeps the needs of current and future generations, as it ensures research analyzing the results of the sustainable development of the Republic of Iraq indicators and comparing the Millennium Development Goals and with the strategic plan and the search is over a set of conclusions and recommendations.